-bc-cx=-S+bx

Simple and best practice solution for -bc-cx=-S+bx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -bc-cx=-S+bx equation:


Simplifying
-1bc + -1cx = -1S + bx

Solving
-1bc + -1cx = -1S + bx

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1bx' to each side of the equation.
-1bc + -1bx + -1cx = -1S + bx + -1bx

Combine like terms: bx + -1bx = 0
-1bc + -1bx + -1cx = -1S + 0
-1bc + -1bx + -1cx = -1S

Add 'cx' to each side of the equation.
-1bc + -1bx + -1cx + cx = -1S + cx

Combine like terms: -1cx + cx = 0
-1bc + -1bx + 0 = -1S + cx
-1bc + -1bx = -1S + cx

Reorder the terms:
S + -1bc + -1bx + -1cx = -1S + cx + S + -1cx

Reorder the terms:
S + -1bc + -1bx + -1cx = -1S + S + cx + -1cx

Combine like terms: -1S + S = 0
S + -1bc + -1bx + -1cx = 0 + cx + -1cx
S + -1bc + -1bx + -1cx = cx + -1cx

Combine like terms: cx + -1cx = 0
S + -1bc + -1bx + -1cx = 0

The solution to this equation could not be determined.

See similar equations:

| c=200+6x | | 2/3x+15=12 | | 9-8p-1=45 | | 3x+5=x(x-1) | | X^2-5x+5=2x^2+7x+6 | | (2x^3y^3/2)/(x^-.5y^2)^-2 | | y=3sinx-4cos^3x | | 4a+b+4c=9 | | X^2-5=2x^2+7x+6 | | (-27/64)^-2/3 | | n+18+2n=90 | | S=bx-bc+cx | | ((2m^3*n^5)/(4n^3))^4 | | (27x)^(2/3)(3x^(6/5)) | | 5v/9=10 | | 7/2w=42 | | Y=-8+27X+20X^2 | | f(x)=7x/3x-9 | | Y=20X^2+27X-8 | | 7+7x=4(5x+2)-1 | | x+a=a+1 | | 140+2x=-120-11x | | Y=9x^2-9x+2 | | 5a-4=3a+36 | | 2X+25=X+32 | | 7a+7a^2+14b^2= | | x^2+(4k-8)*x-16=0 | | 2n+4=30 | | 3x+3(x-8)=6x-2(x-10) | | x+1=2a-2 | | 6(y+8)-8y=32 | | -4+10+2x=10 |

Equations solver categories